Mobile antenna systems handbook - Fujimoto, K. (Kyōhei), 1929- (Artech House antennas and propagation library., 2008)
This extensively revised and expanded edition of the Artech bestseller Mobile Antenna Systems Handbook puts the very latest technologies, design and analysis procedures, and applications at your command. It features all-new chapters on smart antennas, MIMO systems, and antennas for recently deployed mobile systems such as RFID, UWB, and terrestrial digital TV broadcasting, and provides a wealth of problem-solving guidance for tackling everything from propagation obstacles to SAR safety issues. Like the previous editions, this ultimate one-stop reference is designed to save you a mountain of work. You get hands-on expertise for every type of mobile antenna base station and terminal system, including its theory of operation, application strengths and weaknesses, performance characteristics, design procedures, analysis techniques, and optimization methods, complete with examples and worked-out calculations at every step. The material is further clarified with 567 diagrams, charts, and photos, bringing mobile antenna selection, design, and construction into clear focus. What's more, this resource includes a detailed glossary of antennas and their applications to help you zero in on the right antenna for any job with a flip of the page. From integrating MIMO antennas into handsets, to expanding system capacities with smart antennas, this information-packed resource helps you evaluate design and configuration options, locate crucial data and calculations, perform key analyses, and solve challenges standing in the way of your desired results. It serves as an indispensable reference, helping you design more powerful, versatile, and compact wireless mobile antenna systems.